2021
DOI: 10.1177/15501477211028399
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient distributed heterogeneous clustered spectrum-aware cognitive radio sensor network for guaranteed quality of service in smart grid

Abstract: The development of a modern electric power grid has triggered the need for large-scale monitoring and communication in smart grids for efficient grid automation. This has led to the development of smart grids, which utilize cognitive radio sensor networks, which are combinations of cognitive radios and wireless sensor networks. Cognitive radio sensor networks can overcome spectrum limitations and interference challenges. The implementation of dense cognitive radio sensor networks, based on the specific topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…However, the mesh topology has higher complexity and energy consumption with minimal delay. Detailed discussions on the network topologies including their merits and demerits can be found in [40][41][42].…”
Section: Lpwan Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the mesh topology has higher complexity and energy consumption with minimal delay. Detailed discussions on the network topologies including their merits and demerits can be found in [40][41][42].…”
Section: Lpwan Architecturementioning
confidence: 99%
“…In rural or open space setting the connectivity, the range is over 40 km. However, only 140 uplink messages with a payload of 12 bytes and up to 4 downlink messages with each a payload of 8 bytes per day can be communicated through Sigfox [41]. Sigfox network reliability can be improved by using a time and frequency variation strategy with multiple transmissions [45].…”
Section: • Sigfoxmentioning
confidence: 99%
“…Even though high effective measures and resources are allocated for converting the grid to be smart, only few researchers have addressed the problem in a precise way . In recent networking structure [34,35], research gap on smart grid networks with high cost of installation is observed, and in other developed models, a crucial task on minimization of power with better quality of service with constraints such as distortion and transmission delivery rates has not been solved in an accurate manner. However, all the procedures enumerated grieves from any one drawback.…”
Section: Research Gap and Motivationmentioning
confidence: 99%
“…e primary objective on minimizing the total power that is consumed by each node can be calculated by optimizing the transmitted and encoded power in addition to source rate at each node. Also, high quality of video can only be achieved if the power consumption is increased at all corresponding nodes, which is not discussed and calculated in [34]. e objective of power minimization is given in:…”
Section: Minimization Of Powermentioning
confidence: 99%
See 1 more Smart Citation